Tobacco Use and Adolescents in Indonesia: Narrative Review of Determinants - Rukmi, S (KnE Life Sciences, 2019)
In 2013, Indonesia had over 60 million smokers that made this country in the third highest number of tobacco users in the world. The Global Youth Tobacco Survey 2014 revealed that there were 20.3% of adolescents aged 13-15 smoked tobacco products. Teen smokers are risky to become addicted to nicotine and suffer from tobacco-related diseases such as respiratory and cardiovascular system damage. Ultimately, these health consequences reduce the youths’ productivities. A better and comprehensive understanding of factors related to tobacco use in children is critical to promote more comprehensive approaches in reducing the high prevalence of smoking, addressing health inequalities, accelerating health, social, and economic impacts. This paper aimed to review the determinants of tobacco use among adolescents in Indonesia which were prominent for forwarding tobacco control interventions. Systematic search literature undertakes through journal databases including PubMed, Medline (Ovid), Scopus, ProQuest, Web of Science, PsycINFO, Google Scholar, websites of the MoH, WHO, and CDC. Content and thematic analysis employed among final selected papers. Tobacco use among adolescents in Indonesia was associated with socio-demographic determinant including age, sex, family structure, pocket money, parents’ education, parental employment, grade, school area; personal determinants including curiosity, self-efficacy, attitude, positive perception of tobacco consumption effect on the mind, belief that smoking was functional; behavioural determinants including class absent, academic score, physical activities; environmental determinants including having friends, peers, parents, sibling who smoked, family function, accessibility, availability and affordability of tobacco products, social factors, cigarette advertising. There were disparities across socio-demographic factors between smokers and non-smokers — moreover, personal and behavioral determinants of smoking among adolescents mainly influenced by the environment. Behavioral changes were necessary to improve health outcomes. However, socio-environmental approach such as building healthy public policy was also needed. Tobacco control legislation could encourage social, environmental, and system changes. Moreover, they had a broader action to reduce health disparities and more sustained impact on social determinants of health than intervention which focus on individuals. Keywords: Tobacco use; determinant; adolescent; Indonesia